CORPORATE SOCIAL RESPONSIBILITY SEBAGAI MANIFESTASI ETIKA BISNIS SYARIAH: ANALISIS NORMATIF DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Muhammad Zainal Arifin (JSE: Jurnal Sharia Economica, 2026)
Corporate Social Responsibility (CSR) has become an increasingly important concept in modern business practices as a manifestation of corporate responsibility toward social, economic, and environmental concerns. Despite its growing adoption, CSR remains subject to debate because its implementation is often driven by corporate reputation, legitimacy, and regulatory compliance rather than substantive moral responsibility. This study aims to analyze CSR as a manifestation of Islamic business ethics from the perspective of Islamic Economic Law. Employing a qualitative approach, this research adopts a library research design with a normative-conceptual framework. Data were collected through document analysis of scholarly books, journal articles, international guidelines, and relevant fatwas related to CSR, Islamic business ethics, and maqāṣid al-sharī‘ah. The data were analyzed using content analysis, with maqāṣid al-sharī‘ah serving as the primary analytical framework. The findings reveal that CSR demonstrates strong conceptual compatibility with the principles of Islamic business ethics, particularly in terms of justice (al-‘adl), trustworthiness (amanah), social responsibility, and public welfare (maṣlaḥah). However, CSR and Islamic business ethics differ in their philosophical foundations. Modern CSR is primarily rooted in stakeholder and corporate sustainability paradigms, whereas Islamic business ethics is grounded in the principles of tawḥīd, stewardship (khilāfah), and accountability before God. The study further finds that an orientation toward public welfare constitutes the key criterion distinguishing Sharia-based CSR from corporate-oriented CSR. Moreover, maqāṣid al-sharī‘ah provides a comprehensive normative framework for evaluating the substance and effectiveness of CSR programs. The study concludes that CSR can be positioned as an operational manifestation of Islamic business ethics that actualizes the values of justice, trustworthiness, social responsibility, and public welfare within contemporary business practices.